NEW SPECIES OF EGG-PARASITIZING WASPS OF THE GENUS IDRIS (SCELIONIDAE, PROCTOTRUPOIDEA) OF THE ROVNO AMBER - Kononova S.V. (My University, 2003)
New scelionid species of the genus Idris Förster, I. affinis sp. nov., I. exilis sp. nov., and I. gracilis sp. nov., are described from the Rovno amber, Ukraine. The origin and distribution of the Rovno amber are discussed.